Determination of Vitamin C and Metal Copper (Cu) Levels in Katokkon Chili (Capsicum chinense Jacq) Based on Maturity Level - Novianti Patiung; Daud K. Walanda; Sitti Aminah (Universitas Tadulako, 2021)
Katokkon chili is one type of chili grown mainly in the Tana Toraja district, and the people use this plant as a typical spice with variations colors from green, orange, and red. It is assumed that the plant is rich in vitamins and minerals. This study aims to determine the levels of vitamin C and copper metals in katokkon chili based on their level of maturity. Vitamin C and copper levels were determined by spectrophotometry. The results showed that the highest level of vitamin C was 23.52 and 5.12 mg/kg in both wet and dry orange chilies, while the highest copper level was found in green chili was 12.25 mg/kg